Cross-Cultural Validation of Children's Assessment of Participation and Enjoyment Portuguese Version - Vila-Nova, Fábio; Oliveira, Raul; Cordovil, Rita (Frontiers in Pediatrics, 2019)
Background: Participation is a major pediatric rehabilitation goal according to The International Classification of Functioning, Disability and Health Children and Youth version (ICF-CY). ICF-based leisure participation measures for Portuguese-speaking children with cerebral palsy are currently not available. The aim of this study is to assess validity and reliability of the Portuguese (European) version of the Children’s Assessment of Participation and Enjoyment (CAPE). Methods: CAPE Portuguese version was applied to 170 children with cerebral palsy (n = 69) and typical development (n = 101) aged between 8 and 18 years (mean = 12.5 years; SD = 2.91). Construct validity was assessed by using the know-groups method and by analyzing the correlation between participation and quality of life. Reliability was determined by internal consistency and test-retest. Results: CAPE discriminates between participation scores of children with cerebral palsy and typical development. Positive correlations were found between participation and physical and psychological well-being domains. Internal consistency was not entirely satisfactory but comparable with that from the original CAPE study. Test-retest reliability was considered good. Conclusions: CAPE Portuguese (European) version showed satisfactory validity and test-retest reliability to assess leisure participation in children with cerebral palsy and typical development aged between 8 and 18 years.